Functioning performance trajectory and its associated factors for people with disability—A 4-year national study - Tzu-Ying Chiu; Tsan-Hon Liou; Chia-Feng Yen (BMC Public Health)
Abstract Background Humans experience functioning difficulties in daily life, which are dependent on the interaction between health conditions and barriers in life. In general, functioning is an umbrella term and a dynamic concept. Thus, identifying the factors associated with long-term functioning would be beneficial to the development of specific health policies and quality of life for people with disabilities. However, previous studies are mainly cross-sectional ones, and fewer studies focus on the long-term effect of changes in functioning for people with disabilities. The current study aims to examine functioning performance trajectory and the associated factors for people with disabilities. Methods A longitudinal study was conducted over four years, for which data were retrieved from the National Disability Eligibility Determination System in Taiwan. The assessment methods used are as follows: activity and participation rated using the WHO Disability Assessment Schedule 2.0 (with high scores indicating increased limitations in daily life), personal factors, body function and structure, and environmental factors. Statistical analysis was conducted using latent growth curve models. Results We recruited 3,720 people with disabilities. We found that females, people with moderate and severe disability level, and those who were employed were associated with rapid increases in functioning scores every year. Conversely, improved social participation was linked to relatively slow increases in functioning scores regardless of the type of disability (p <.05). Conclusions Determining the factors associated with long-term functioning can serve as a reference for the development of health policies and improvement of quality of life for people with disabilities.